An overview on the validation of the name Andrographis longipedunculata (Acanthaceae) - Gnanasekaran, Gunadayalan; Arisdason, Wilson; Deng, Yunfei (Phytotaxa, 2020)
Neesiella Sreemadhavan (1967: 270) was established by Sreemadhavan (1967) as a new genus to accommodate 4-seeded species those were previously placed in the genus Andrographis Wall. ex Nees (1832: 116), namely N. echioides (L.) Sreemadhavan (1967: 271), originally published as Justicia echioides Linnaeus (1753: 16), and a new species N. longipedunculata Sreemadhavan (1967: 271). Later, Sreemadhavan (1968) found that Neesiella is a later homonym of a bryophyte genus Neesiella Schiffner (1893: 32) and therefore proposed a substitute name, Indoneesiella Sreemadhavan (1968: 466).